Fundamentals of television engineering - Glasford, Glen M. (McGraw-Hill, 1955)
Television today means moving pictures in colour with sound, brought to the viewer by terrestrial or satellite broadcast, cable or recording medium. The technique and processes necessary to create, record, deliver and display television pictures form the major part of this book.